Contextual Crossword: A Gamified Approach to Slang Acquisition and Critical Thinking Skills - Fitri, Nabila Nur; Agustina, Eliasanti; Setiawan, Rahmat (Universitas Nurul Jadid, 2025)
This study addresses the effectiveness of contextualized crossword puzzles as a gamified learning tool for developing slang and critical thinking skills among EFL college students. Motivated by gaps in traditional English language teaching, which often exclude informal language and higher-order thinking, this study implemented slang-focused vocabulary learning with critical thinking through a contextualized crossword puzzle format. A mixed-methods explanatory approach was used, combining quantitative data from 50 students via a Likert scale survey and qualitative insights from interviews with 3 participants with varying levels of achievement. Quantitative findings showed high levels of students' agreement with the usefulness of the activity in developing slang comprehension, engagement, and analytical reasoning. The qualitative results further revealed that the students found the puzzles intellectually challenging, engaging, and useful for problem solving and logical reasoning. Five main themes emerged: engagement and fun, vocabulary acquisition, critical thinking development, overcoming challenges, and problem solving. These findings are in line with constructivist learning theory and Bloom’s Taxonomy, which stated that crosswords provide meaningful cognitive engagement while encouraging real-world language use. This study emphasizes the importance of incorporating gamification strategies into the EFL classroom and suggests contextualized crosswords as a practical, motivating, and educational medium to unify formal learning with informal, everyday communication.